Frontiers in Biosciences and Biotechnology: Bridging Theory and Application - Hussein, Yousif Karim; Hadi, Marwa Mohammed; Zaghir, Ali Hamad; Kadhem, Muna Hadi; Harran, Ziad Ali (American Journal of Biology and Natural Sciences, 2025)
Biosciences and biotechnology have revolutionized scientific understanding and applications in medicine, agriculture, and environmental sustainability. Despite rapid advancements, a persistent gap exists between theoretical research and its real-world applications, particularly in integrating emerging biotechnologies with practical solutions. This paper reviews historical, technical, and interdisciplinary developments across molecular biology, genetic engineering, biopharmaceuticals, and bioinformatics, emphasizing the need to align scientific innovation with societal and ethical considerations. By adopting a systems-based and cross-disciplinary analytical approach, the study maps current trends and explores tools such as CRISPR, synthetic biology, gene therapy, and bioremediation. The implications suggest that fostering synergy between theoretical models and applied technologies is essential to address global challenges in health, food security, and environmental conservation, paving the way for sustainable and ethically guided biotechnological innovations.